Indigenous Knowledge of Communities of Achanakmar-amarkantak Biosphere Reserve in Utilization, Conservation and Sustainability of NTFP in Chhattisgarh (India) - Bhat, Shabir Ahmad; Tiwari, Subhash Chandra (Indian Forester, 2011)
Indigenous knowledge plays an important role in sustainable development, being planned by scientists and planners who are striving for tribal development. The present paper examines indigenous knowledge and its importance in utilization, conservation and management of natural resources among primitive tribal populations like Gond, Baiga, Kanwar, Uraon, Bharia and Pahadi korwa of Chattissgarh with special reference of Achanakmar-Amarkantak Biosphere Reserve. There is an urgent need to document the existing indigenous knowledge of these deserted groups before it is totally lost and also to evaluate its value for bio-diversity conservation. Indigenous knowledge may contribute to improved development strategies in several ways such as by helping identify cost-effective and sustainable mechanisms for poverty alleviation that are locally manageable and meaningful; by a better understanding of the complexities of sustainable development in its ecological and social diversity; and by helping to identify innovative pathways to sustainable human developmentthat enhance local communities and their environments.